On-Line Calculation of Pulmonary Mechanics by Digital Computer - Lorino, H.; Brault, Y.; Harf, A.; Atlan, G.; Lorino, A.-M.; Laurent, D. (Methods of Information in Medicine, 1978)
A system was built up around a minicomputer to process in real time pressure and flow signals collected during the course of three ventilatory mechanics tests: the calculation of the lung volume, the evaluation of the static lung compliance, the analysis of the forced expiratory performance. The subject is seated in an open body Plethysmograph, which allows for the instantaneous calculation of changes in the volume of his thorax and abdomen. The system is controlled through a graphics console which displays the sampled curves and the results of data processing. In addition, the signals can be stored on demand onto a magnetic tape so that the method can be tested and improved off line. The results obtained in healthy volunteers are highly reproducible. A close correspondence is found both in patients and volunteers between computer-derived and hand-calculated results. The computerized system has become a standard equipment of our Lung Function Department, where it allows for a rapid quantitative analysis of lung volumes, lung elasticity and bronchial airflow.
Keywords: Body Plethysmography; Forced Expiration; Computer Processing of Lung Test Data